Geometric and Electronic Properties of Edge-decorated Graphene Nanoribbons - Chang, Shen-Lin (Nature Publishing Group, 2014)
Edge-decorated graphene nanoribbons are investigated with the density functional theory; they reveal three stable geometric structures. The first type is a tubular structure formed by the covalent bonds of decorating boron or nitrogen atoms. The second one consists of curved nanoribbons created by the dipole-dipole interactions between two edges when decorated with Be, Mg, or Al atoms. The final structure is a flat nanoribbon produced due to the repulsive force between two edges; most decorated structures belong to this type. Various decorating atoms, different curvature angles, and the zigzag edge structure are reflected in the electronic properties, magnetic properties, and bonding configurations. Most of the resulting structures are conductors with relatively high free carrier densities, whereas a few are semiconductors due to the zigzag-edge-induced anti-ferromagnetism.